Une mission en Perse. 1897-1912 (1997)
Beiträge von Pierre Amiet, Béatrice André-Salvini, Agnès Benoit, Marthe Bernus-Taylor, Nicole Chevalier, John Curtis, Dominique Gerin, Hermann Gasche, Guillermina Joel, Christine Lorre, Jean Perrot, Agnès Spycket, Françoise Tallon